Analisis Upah Kerja Lembur pada PT. Arum Raya - Camelia Verahastuti3, Krisna Dwi Wicaksono1 Edy Soegiarto K2 (EKONOMIA, 2021)
ABSTRACT          This research aims to determine the calculation of overtime pay for employees of PT. Arum Raya in January 2019 and the formulation of the problem in this study  is whether the calculation of overtime wages applied by PT. Arum Raya is lower than the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia No. Kep. 102 / MEN / VI / 2004 and Decree of the Governor of East Kalimantan Province Number 561 / K.594 / 2018.          The theory used in this research is cost accounting. The analysis tool used in this study is a comparative method, which compare the results of overtime wage calculations based on the Decree of the Minister of Manpower and Transmigration RI No. Kep. 102 / MEN / VI / 2004 and Decree of the Governor of East Kalimantan Province Number 561 / K.594 / 2018 with calculations based on PT. Arum Raya.          The results  showed that PT. Arum Raya in apply overtime wages has lower than the Decree of the Minister of Manpower and Transmigration Decree No. RI. Kep. 102 / MEN / VI / 2004 and Decree of the Governor of East Kalimantan Province Number 561 / K.594 / 2018.          The conclusion of this study is the overtime pay applied by PT. Arum Raya is lower than the Decree of the Minister of Manpower and Transmigration of RI No. Kep. 102 / MEN / VI / 2004 and Decree of the Governor of East Kalimantan Province Number 561 / K.594 / 2018, so the researcher's hypothesis is accepted.